Role of Macrophages in Resistance to Murine Cytomegalovirus - Selgrade, Maryjane K. (1974)
The role of macrophages in protecting mice from murine cytomegalovirus (MCMV) was studied in Swiss, CBA/J, and C57BL/6J mice. CBA/J mice were more resistant to virus than were C57BL/6J mice at all ages tested. Prior treatment of adult Swiss mice with 60 mg of silica, a dose selectively toxic to macrophages, increased mortality due to MCMV infection. Transfer of syngeneic adult macrophages to suckling mice significantly increased their resistance to subsequent MCMV infection. Transfer of syngeneic, nonimmune adult lymphocytes to suckling mice also had a lesser but significant protective effect against subsequent MCMV challenge. In vitro infection of adult CBA/J and C57BL/6J macrophages with virulent and attenuated MCMV resulted in productive infection in only a small percentage of cells and recovery of very little virus from the extracellular fluid. Infection of CBA macrophages was no less productive than C57BL/6J nor was infection with virulent virus more productive than with attenuated virus. Histological examination of the livers of MCMV-infected CBA/J and C57BL/6J mice suggested that divergent cellular immune responses to infection might account for differences in susceptibility. It is postulated that the macrophage may facilitate the inductive phase of cellular immunity, one possible explanation for its demonstrated importance in host defenses against MCMV.